A competitive enzyme-linked immunosorbent assay for rapid detection of antibodies against Trichinella spiralis and T. britovi – one test for humans and swine. Issue 1 (23rd January 2019) - Gnjatovic, M.; Gruden-Movsesijan, A.; Miladinovic-Tasic, N.; Ilic, N.; Vasilev, S.; Cvetkovic, J.; Sofronic-Milosavljevic, Lj.
Abstract: Infection with parasites from the Trichinella genus occurs in many vertebrates but disease only occurs in humans (trichinellosis). Humans are infected after the consumption of raw or undercooked meat from infected wild or domestic animals (usually swine or horses). Using the monoclonal antibody (mAb) 7C2C5, specific for an epitope unique to the muscle larvae of the genus Trichinella, we have developed a competitive enzyme-linked immunosorbent assay (c-ELISA) that enables the rapid detection of Trichinella -specific antibodies in sera originating from two different host species (human, swine) infected with either Trichinella spiralis or Trichinella britovi . This novel c-ELISA exhibited 100% specificity and sensitivity, as confirmed by a Western blot test. The assay is easy to use (one incubation step), and the time required for the procedure (45 min) is shorter than in any other ELISA format. This test could be useful for both the detection and surveillance of Trichinella infections.